(untitled) (Hilo Analítico, 2025)
Health psychology is an applied field of psychology that, historically, has been confused with clinical psychology, although they are not the same. Both share activities such as health promotion and disease prevention, their roles are distinct. Health psychology includes other tasks that differ significantly from clinical roles. This reflection will focus on those specific roles and how they can contribute to social change within health psychology.